Combining segments 9 and 10 in DNA and recombinant protein vaccines conferred superior protection against tilapia lake virus in hybrid red tilapia (oreochromis sp.) compared to single segment vaccines - Chamtim, Pitakthai; Suwan, Eukote; Dong, Ha Thanh; Sirisuay, Soranuth; Areechon, Nontawith; Wangkahart, Eakapol; Hirono, Ikuo; Mavichak, Rapeepat; Unajak, Sasimanas (Frontiers in Immunology, 2022)
Tilapia lake virus (TiLV) now affects Nile tilapia culture worldwide, with no available commercial vaccine for disease prevention. DNA and recombinant protein-based vaccines were developed and tested following viral isolation and characterization. The viral strain isolated from diseased hybrid red tilapia (Oreochromis sp.) shared high levels of morphological and genomic similarity (95.49-99.52%) with other TiLV isolates in the GenBank database. TiLV segment 9 (Tis9) and segment 10 (Tis10) DNA vaccines (pcDNA-Tis9 and pcDNA-Tis10) and recombinant protein vaccines (Tis9 and Tis10) were prepared and tested for their efficacy in juvenile hybrid red tilapia. Fish were immunized with either single vaccines (pcDNA-Tis9, pcDNA-Tis10, Tis9 and Tis10) or combined vaccines (pcDNA-Tis9 + pcDNA-Tis10 and Tis9 + Tis10) by intramuscular injection and intraperitoneal injection for DNA and protein vaccines, respectively. Negative controls were injected with PBS or a naked pcDNA3.1 vector in the same manner. An experimental challenge with TiLV was carried out at 4 weeks post-vaccination (wpv) by intraperitoneal injection with a dose of 1 × 105 TCID50 per fish. Relative percent survival (RPS) ranged from 16.67 ± 00.00 to 61.11 ± 9.62%. The Tis10 and pcDNA-Tis10 vaccines conferred better protection compared to Tis9 and pcDNA-Tis9. Highest levels of protection were observed in pcDNA-Tis9 + pcDNA-Tis10 (61.11 ± 9.62%) and Tis9 + Tis10 (55.56 ± 9.62%) groups. Specific antibody was detected in all vaccinated groups at 1-4 wpv by Dot Blot method, with the highest integrated density at 2 and 3 wpv. In silico analysis of Tis9 and Tis10 revealed a number of B-cell epitopes in their coil structure, possibly reflecting their immunogenicity. Findings suggested that the combination of Tis9 and Tis10 in DNA and recombinant protein vaccine showed high efficacy for the prevention of TiLV disease in hybrid red tilapia.